Respuesta :
Answer: x = 2
Step-by-step explanation:
Let's solve your equation
x + 16/3 = 3x
Step 1: Simplify both sides of the equation:
x + 16/3 = 3x
1/3x + 16/3 = 3x (Distribute)
Step 2: Subtract 3x from both sides:
1/3x + 16/3
- 3x
= 3x + 3x
= -8/3x + 16 = 0
Step 3: Subtract 16/3 from both sides:
-8/3x + 16/3
- 16/3
= 0 - 16/3
-8/3x = -16/3
Step 4: Multiply both sides by 3/(-8).
(3/−8) * (−8/3x) = ( 3/−8) * ( −16/3)
Answer = x = 2
In the final analysis, ( x + 16/3) = 3x ends up to be x = 2.
Source: https://www.mathpapa.com/calc/tutorial/solving-systems-of-equations/
, Hope this helps :)
Have a great day!!